1973
DOI: 10.1111/j.1469-7610.1973.tb01180.x
|View full text |Cite
|
Sign up to set email alerts
|

The Draw‐a‐man Test: A Study of Scoring Methods, Validity and Norms With English Children at Five and Eleven Years

Abstract: SUMMARY The performance of samples of English children at five and eleven years on the Draw‐a‐Man test is assessed by the scoring methods of Goodenough and Harris. Proposals are made for improving definitions of some scoring instructions. Inters‐corer reliabilities are reported. Average scores of the samples are compared to American norms. Relationships between scores on this test and other cognitive and educational tests arc interpreted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Shortcomings in the construction of the Quality scales have been discussed by several authors. Noting the wide range of Quality scores assigned by several judges to a single drawing, Phillips, Smith, and Broadhurst (1973) commented on the difficulty in making global judgments of quality in drawings in which features anomalous to the drawer's age are present. Attention to these atypical features may produce incorrect scores, especially among judges with little prior ex- perience with the Point scales.…”
Section: Quality Scalementioning
confidence: 99%
See 2 more Smart Citations
“…Shortcomings in the construction of the Quality scales have been discussed by several authors. Noting the wide range of Quality scores assigned by several judges to a single drawing, Phillips, Smith, and Broadhurst (1973) commented on the difficulty in making global judgments of quality in drawings in which features anomalous to the drawer's age are present. Attention to these atypical features may produce incorrect scores, especially among judges with little prior ex- perience with the Point scales.…”
Section: Quality Scalementioning
confidence: 99%
“…Examination of scorer's disagreements item by item has revealed systematic errors that reflect ambiguity in the scoring criteria for some items (Phillips et al, 1973;Sinha, 1970). Phillips et al listed 12 items they found to be vaguely defined, along with their clarification of the scoring criteria for them.…”
Section: Interscorer Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, assessment of young children's emotions, perceptions of social relationships, and future thinking has involved asking them to draw, complete stories or sentences, or describe pictures (Murray, 1943;Phillips, Smith & Broadhurst, 1973). These approaches require interpretation of the child's response by an adult.…”
Section: Methodological Challenges To Instrument Development For Younmentioning
confidence: 99%
“…Normal Nigerian children have a mean score of about 100 on this test (Nwanze, 1981;Nwanze & Okeowo, 1980), indicating that Nigerian children between 6 and 9 years old do not perform very differently from the American children on which the test was originally standardized. The test, moreover, is easy to administer, correlates moderately well with other intelligence tests, and, because it is nonverbal, was convenient to use because the subjects had a variety of primary languages (Philips, Smith, & Broadhurst, 1973). The Draw-A-Man Test was administered according to the instructions outlined in the testing manual.…”
Section: Methodsmentioning
confidence: 99%